Potential thresholds of critically increased cardiac-related spinal cord motion in degenerative cervical myelopathy - Pfender, Nikolai; Jutzeler, Catherine R.; Hubli, Michèle; Scheuren, Paulina S.; Pfyffer, Dario; Zipser, Carl M.; Rosner, Jan; Friedl, Susanne; Sutter, Reto; Spirig, José M.; Betz, Michael; Schubert, Martin; et al. (Frontiers in Neurology, 2024)
Introduction: New diagnostic techniques are a substantial research focus in degenerative cervical myelopathy (DCM). This cross-sectional study determined the significance of cardiac-related spinal cord motion and the extent of spinal stenosis as indicators of mechanical strain on the cord. Methods: Eighty-four DCM patients underwent MRI/clinical assessments and were classified as MRI+ [T2-weighted (T2w) hyperintense lesion in MRI] or MRI-(no T2w-hyperintense lesion). Cord motion (displacement assessed by phase-contrast MRI) and spinal stenosis [adapted spinal canal occupation ratio (aSCOR)] were related to neurological (sensory/motor) and neurophysiological readouts [contact heat evoked potentials (CHEPs)] by receiver operating characteristic (ROC) analysis. Results: MRI+ patients (N=31; 36.9 %) were more impaired compared to MRI-patients (N=53; 63.1%) based on the modified Japanese Orthopedic Association (mJOA) subscores for upper (MRI+ [median (Interquartile range)]: 4 (4-5); MRI-: 5 (5-5); p<0.01) and lower extremity (MRI+: 6 (6-7); MRI-: 7 (6-7); p=0.03) motor dysfunction and the monofilament score (MRI+: 21 (18-23); MRI-: 24 (22-24); p<0.01). Both patient groups showed similar extent of cord motion and stenosis. Only in the MRI-group displacement identified patients with pathologic assessments (trunk/lower extremity pin prick score (T/LEPP